Colonial Legacy and Industrialization: Historical Determinants in the Formation of Local Government Institutions - Haryo Setyoko; Arif Nugroho (Jurnal Multidisiplin Sahombu, 2025)
This article examines the historical interaction between colonialism and industrialization as primary determinants in shaping the structure and performance of local governments in post colonial countries. Based on comparative studies and empirical literature, the findings reveal that both direct and indirect colonial models, along with the degree of industrialization, significantly influence fiscal capacity, public participation, and the level of centralization in local governance. Countries with an indirect colonial legacy and early industrialization tend to develop more adaptive and inclusive local governments, whereas direct colonial models without accompanying industrialization tend to reinforce centralization and weaken institutional capacity. These findings underscore that contemporary local institutional designs cannot be fully understood without considering the structural legacies of the colonial and industrialization periods.